Literasi Pengelolaan Keuangan Sebagai Bentuk Pengabdian Masyarakat di Desa Kalisidi Kabupaten Semarang - Endang Suhendar; Ambar Tri Hapsari; Siti Suaedah; Diah Mariana; Atfal Murodif (Jurnal Informasi Pengabdian Masyarakat, 2024)
The aim of this research is to provide understanding and training for financial management literacy participants in Kalisidi Village, Semarang Regency so that they are able to understand the importance of financial management so that there are no irregularities or errors in village financial traffic. The method used in this research uses a qualitative approach where the target participants are officials, the community and figures in Kalisidi village who participate in managing village finances. The results of this research found that Kalisidi Village still has not optimized resource utilization, while the obstacle in managing village finances is the limited number of competent human resources. The Financial Management Literacy Program carried out is packaged in the form of Community Service so that it can reach every level of the Kalisidi village community. So it can be concluded that Financial Management Literacy is very important for village growth and management so that it can generate profits for the village and improve the welfare of its community.